Political policy education budget government of Yogyakarta, Indonesia - Rohman, Arif; Widowati, Asri (LPMPP Universitas Negeri Yogyakarta, 2024)
This study aims to describe the politics of the education budget in the city of Yogyakarta. This research uses a qualitative approach to phenomenological in the city of Yogyakarta. The subject of the study is chosen purposively from the executive and legislative elements. Excavation of data through in-depth interviews and analysis of documents. The triangulation is used by triangulation of methods and sources, expert discussions, and rival explanations. A qualitatively phenomenological data analysis with data steps managing, reading and memoing, describing, classifying, interpreting, and visualizing. Research findings showed that the 2014 Yogyakarta city education budget was Rp. 432,883,644,325.00. The pattern of distribution and allocation of education budgets is managed based on the coordination and integration of policies between government units. The priorities of the 2014 education budget are determined based on considerations of aspects of urgency and emergency. Priority mainly includes employee salaries,12-year compulsory education programs, and educational development programs.